Data analytics in performance of kick-out distribution and effectiveness in senior championship football in Ireland - Daly, D.; Donnelly, R. (Journal of Sports Analytics, 2018)
In recent years, data analytics has been a growing phenomenon in many fields, including sport, and there has been an increased focus on how technology will impact the work of coaching and performance professionals. This paper provides a reflection of the use of data analytics within the Gaelic Athletic Association`s (GAA) football coaching practice in Ireland, and evaluates for coaches how to enhance kick-out distribution and effectiveness. Specifically, the study aimed to dissect and analyse kick-out strategies to assess from a coaching perspective, the impact on distribution and effectiveness. The research is a result of the modern day professional approach taken by most GAA Inter County teams, and intends to fill the research gap of performance analysis within the context of Gaelic Football. Video analysis of eight Men`s Inter-County Ulster Senior Gaelic Football Championship matches was completed using video analysis software. The key parameter of investigation was kick-outs, with distance and direction being the variables specifically analysed. Three factors were established to measure kick-out effectiveness: retaining possession, attack building, and score/scoring opportunity. A questionnaire was devised for data collection with 75 players and 25 coaches to gather opinions and add further depth to the statistical evidence. Kick-outs to the wings (57.6%) and 65m+ (53.8%) were the most common distribution strategy employed by goalkeepers. Kick-outs to 21-45?m produced notably greater success rates of possession retention (87%) and attack building (55%) than the longer kick-outs. Kick-outs to the wings contributed an 8% greater success rate of creating scoring opportunities as opposed to central kick-outs. Kick-outs to the centre were the only parameter to result in a negative net difference of scores between both teams (-1%). It was established that kick-outs can be successful attacking elements when used efficiently. Short kick-outs to the wings appear to be the most effective strategy to improve the likelihood of possession retention, attack building and creation of scoring opportunities. An implication of this study for sports science is to make data analytics more accessible to GAA coaches, and address the challenges faced by coaches in this area by translating knowledge of performance analysis of kick-outs into working practice on the field.